Association of Klotho with Coronary Artery Disease in Subjects with Type 2 Diabetes Mellitus and Preserved Kidney Function: A Case-Control Study - Donate-Correa, Javier; Martín-Núñez, Ernesto; Mora-Fernández, Carmen; González-Luis, Ainhoa; Martín-Olivera, Alberto; Navarro-González, Juan F. (International journal of molecular sciences, 2023)
Circulating Klotho levels are significantly reduced in subjects with type 2 diabetes mellitus (T2DM) and in kidney disease patients. In this work, the relationship between Klotho levels and the coronary artery disease (CAD) burden in subjects with T2DM and preserved kidney function was analyzed. For this, we performed a cross-sectional case-control study involving 133 subjects with T2DM and 200 age-, sex- and CAD-incidence-matched, non-diabetic patients undergoing non-emergency diagnostic coronary angiography. All of them were non-albuminuric and with normal glomerular filtration rates. The concentrations of serum Klotho, fibroblast growth factor 23, and inflammatory markers were also measured. As expected, the serum Klotho concentration was lower in the T2DM group (12.3% lower, p = 0.04). However, within the group of patients with T2DM, those subjects with CAD presented significantly higher Klotho levels than those without significant coronary stenosis (314.5 (6.15–562.81) vs. 458.97 (275.2–667.2) pg/mL; p = 0.02). Multiple regression analysis revealed that serum Klotho was positively related with stenosis values exclusively in subjects with T2DM (adjusted R2 = 0.153, p < 0.01). Moreover, logistic regression analysis showed that Klotho was positively associated with the presence of significant CAD in the group of T2DM patients (OR: 1.001; p = 0.041). Our data suggest that higher levels of circulating Klotho in subjects with T2DM and preserved kidney function are associated with the presence of significant CAD.